Chemiosmotic coupling in Methanobacterium thermoautotrophicum: hydrogen-dependent adenosine 5'-triphosphate synthesis by subcellular particles. - Doddema, H J (1979)
Hydrogenase and the adenosine 5'-triphosphate (ATP) synthetase complex, two enzymes essential in ATP generation in Methanobacterium thermoautotrophicum, were localized in internal membrane systems as shown by cytochemical techniques. Membrane vesicles from this organism possessed hydrogenase and adenosine triphosphatase (ATPase) activity and synthesized ATP driven by hydrogen oxidation or a potassium gradient. ATP synthesis depended on anaerobic conditions and could be inhibited in membrane vesicles by uncouplers, nigericin, or the ATPase inhibitor N,N'-dicyclohexylcarbodiimide. The presence of an adenosine 5'-diphosphate-ATP translocase was postulated. With fluorescent dyes, a membrane potential and pH gradient were demonstrated.